Structural steels nitriding in low-pressure gas discharge; Fizika i Khimiya Obrabotki Materialov; № 3 - Shchanin P. M.; Goncharenko I. M.; Grigor'ev S. V.; Koval N. N. Nikolay Nikolaevich (2002, 2002)
Structure, microhardness and tribological properties of the surface layers of structural medium-carbon steels 1045 and 4140 after ion nitriding in low-pressure arc discharge plasma have been studied. Nitriding process was carried out in the chamber without introduced hydrogen at pressure of 10-1 Pa. It was found that under the action of negative voltage applied to the specimen, accelerated ions formed near specimen surface destroy the surface oxide film and heat the specimens up to temperature sufficient high for diffusion. Oxygen partial pressure and ion current density values were established such that surface oxide film preventing nitriding process was not formed. Tribological properties of specimens nitriding in glow and arc discharges have been compared.